2018
DOI: 10.1136/esmoopen-2018-000343
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative chemotherapy with single-agent fluoropyrimidines after resection of colorectal cancer liver metastases: a meta-analysis of randomised trials

Abstract: Surgical resection is the only option of cure for patients with metastatic colorectal cancer. Risk of recurrence after metastasectomy is around 75%. Use of adjuvant chemotherapy after metastasectomy is controversial.AimTo address whether adjuvant systemic therapy after colorectal cancer metastasectomy offers any survival benefit compared with surgery alone.MethodsSystematic review of literature and meta-analysis of all available randomised evidence. Relative hazards (RHs) were summarised across trials and hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…A recent meta-analysis of three randomized trials detected a statistically significant prolonged DFS for patients with CRLM who had received additive CTx in comparison to patients without CTx. However, with regard to patients’ OS a calculation of the survival benefit after additive CTx missed the level of statistical significance closely [ 20 , 29 ]. Other retrospective studies identified a survival advantage of additive CTx for certain patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of three randomized trials detected a statistically significant prolonged DFS for patients with CRLM who had received additive CTx in comparison to patients without CTx. However, with regard to patients’ OS a calculation of the survival benefit after additive CTx missed the level of statistical significance closely [ 20 , 29 ]. Other retrospective studies identified a survival advantage of additive CTx for certain patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated a significantly improved disease-free survival (DFS) after additive chemotherapy (CTx) for patients with CRLM, statistical significance was missing for patients’ OS despite a clearly prolonged median OS [ 19 , 20 ]. In addition, most of the current evidence regarding CRLM includes patients with synchronous and metachronous CRLM resulting in heterogeneous patient cohorts [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Moreover, some studies have reported the nonsignificant effects of adjuvant chemotherapy on OS after LR. [21][22][23] Few recent studies have shown that doublet combination chemotherapy has no significant benefit or even has disadvantages compared with monochemotherapy. [17,24] Moreover, the beneficial effects of additional bioagents with cytotoxic chemotherapy in an adjuvant setting remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite nearly 500 patients being included, only a positive trend for an overall survival advantage was observed from the use of adjuvant chemotherapy. 6 …”
mentioning
confidence: 99%
“…Considering the enormous accrual difficulties encountered in post-metastasectomy trials and the long survival follow-up required in this setting, 6 the scientific community (physicians, health authorities, academia and industry) has to take the necessary concerted actions in order to enrol patients in well-designed and informative trials.…”
mentioning
confidence: 99%